2015
DOI: 10.1002/dmrr.2627
|View full text |Cite
|
Sign up to set email alerts
|

Different health behaviours and clinical factors associated with bone mineral density and bone turnover in premenopausal women with and without type 1 diabetes

Abstract: Background Women with type 1 diabetes (T1DM) have an elevated fracture risk. We therefore compared the associations of health behaviors and clinical factors with bone mineral density (BMD) and bone remodeling between premenopausal women with and without T1DM to inform potential interventions. Methods Participants included women with T1DM (n=89) from the Wisconsin Diabetes Registry Study and age- and race-matched controls without diabetes (n=76). Peripheral (heel, forearm) and central (hip, spine) BMD, marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
2
3
0
Order By: Relevance
“…Findings of lower heel BMD in premenopausal women with type 1 diabetes were consistent with the Wisconsin Diabetes Registry Study by Kujath et al 24 . and the study by Danielson KK et al 25 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Findings of lower heel BMD in premenopausal women with type 1 diabetes were consistent with the Wisconsin Diabetes Registry Study by Kujath et al 24 . and the study by Danielson KK et al 25 .…”
Section: Discussionsupporting
confidence: 87%
“…Findings of lower heel BMD in premenopausal women with type 1 diabetes were consistent with the Wisconsin Diabetes Registry Study by Kujath et al 24 and the study by Danielson KK et al 25 using DXA, and the study by Strotmeyer et al 26 using ultrasound. The reason for the lower BMD in type 1 diabetes patients in the premenopausal period remains unknown.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, body mass index (BMI) does not always correlate with bone health, particularly in diabetic women [ 32 ]. While bone turnover rate may be affected by body weight [ 33 ], body weight does not accurately predict fat mass or lean mass.…”
Section: Reviewmentioning
confidence: 99%
“…However, the association between T1DM and bone mineral density (BMD) is controversial. Some studies have demonstrated a reduced BMD (Pan et al, 2014;Kujath et al, 2015), while others have shown normal or even increased BMD (Gallacher et al, 1993;Maggio et al, 2010) in patients with T1DM compared to control subjects.…”
Section: Introductionmentioning
confidence: 99%